Salmonella Infantis Delays the Death of Infected Epithelial Cells to Aggravate Bacterial Load by Intermittent Phosphorylation of Akt With SopB - Chu, Bing-Xin; Li, Ya-Nan; Liu, Ning-; Yuan, Lan-Xin; Chen, Shi-Yan; Zhu, Yao-Hong; Wang, Jiu-Feng (Frontiers in Immunology, 2021)
Salmonella Infantis has emerged as a major clinical pathogen causing gastroenteritis worldwide in recent years. As an intracellular pathogen, Salmonella has evolved to manipulate and benefit from the cell death signaling pathway. In this study, we discovered that S. Infantis inhibited apoptosis of infected Caco-2 cells by phosphorylating Akt. Notably, Akt phosphorylation was observed in a discontinuous manner: immediately 0.5 h after the invasion, then before peak cytosolic replication. Single-cell analysis revealed that the second phase was only induced by cytosolic hyper-replicating bacteria at 3-4 hpi. Next, Akt-mediated apoptosis inhibition was found to be initiated by Salmonella SopB. Furthermore, Akt phosphorylation increased mitochondrial localization of Bcl-2 to prevent Bax oligomerization on the mitochondrial membrane, maintaining the mitochondrial network homeostasis to resist apoptosis. In addition, S. Infantis induced pyroptosis, as evidenced by increased caspase-1 (p10) and GSDMS-N levels. In contrast, cells infected with the ΔSopB strain displayed faster but less severe pyroptosis and had a less bacterial load. The results indicated that S. Infantis SopB mediated Akt phosphorylation delayed pyroptosis, but aggravated its severity. The wild-type strain also caused more severe diarrhea and intestinal inflammatory damage than the ΔSopB strain in mice. These findings revealed that S. Infantis delayed the cells death by intermittent activation of Akt, allowing sufficient time for replication, thereby causing more severe inflammation.